PENENTUAN SISWA BERPRESTASI KELAS BAHASA DI SMA “EFG” MENGGUNAKAN METODE EDAS - Andra Rizky Afandhi; Putri Aisyiyah Rakhma Devi; Harunur Rosyid (Universitas Islam Balitar, 2022)
Achievement students are one of the references in the level of success in high school. Students who excel in the Language Class at SMA